Engraftment for CD34 selected stem cell products is not compromised by cryopreservation. Issue 4 (12th December 2015) - Reich‐Slotky, Ronit; Bachegowda, Lohith S.; Ancharski, Michael; Gergis, Usama; van Besien, Koen; Cushing, Melissa M.
Abstract : BACKGROUND: The coinfusion of haploidentical CD34+ selected peripheral blood stem cell products with umbilical cord blood (UCB) provides early neutrophil recovery, long‐term UCB engraftment, and a lower incidence of graft‐versus‐host disease; however, this complex transplant presents a scheduling challenge for both the cellular therapy laboratory and the clinical team. Cryopreservation of the haploidentical product can facilitate scheduling, but has been previously shown to be associated with infusion reactions and delayed platelet (PLT) engraftment in allogeneic hematopoietic progenitor cell transplant. STUDY DESIGN AND METHODS: To test whether cryopreservation of the CD34+ selected product compromises the graft, we compared neutrophil and PLT engraftment kinetics for patients receiving freshly infused or cryopreserved products. Seventy‐two products collected from haploidentical related donors were CD34+ selected and infused in a combined transplant with UCB: 32 were cryopreserved before infusion and 40 were infused fresh. RESULTS: No adverse infusion events were reported in either group and there was no difference in neutrophil and PLT engraftment time between fresh and cryopreserved products. CONCLUSION: Cryopreservation of a CD34+‐selected product can be safely used in a combined transplant with UCB and does not affect engraftment time.